Empedobacter brevis Bacteremia in a Patient Infected with HIV: Case Report and Review of Literature - Syed Bokhari; Naeem Abbas; Manisha Singh; Richard B. Cindrich; Cosmina Zeana (Case Reports in Infectious Diseases)
Clinical disease caused by Empedobacter brevis (E. brevis) is very rare. We report the first case of E. brevis bacteremia in a patient with HIV and review the current literature. A 69-year-old man with human immunodeficiency virus (HIV) and CD4 count of 319 presented with chief complaints of black tarry stools, nausea and vomiting for 2 days. Physical exam was significant for abdominal pain on palpation with no rebound or guarding. His total leukocyte count was 32,000 cells/μL with 82% neutrophils and 9% bands. Emergent colonoscopy and endoscopic esophagogastroduodenoscopy showed esophageal candidiasis, a nonbleeding gastric ulcer, and diverticulosis. Blood cultures drawn on days 1, 2, and 3 of hospitalization grew E. brevis. Patient improved with intravenous antibiotics. This case is unusual, raising the possibility of gastrointestinal colonization as a source of the patient’s bacteremia. In conclusion, E. brevis is an emerging pathogen that can cause serious health care associated infections.